El hábeas corpus preventivo y correctivo al amparo de la jurisprudencia de la Corte Constitucional del Ecuador - Paz Jaramillo, María Gabriela (2023)
This academic work is directed towards a legal-doctrinaire study of aspects integrated by constitutional law and criminal law, which have been developed in depth by the Constitutional Court of Ecuador. That is habeas corpus as a guarantee that protects the rights of persons deprived of liberty amid the chaotic scenes that are lived inside the centers of deprivation of liberty. It is from the study of the jurisprudence of the Court that, on the one hand, there are superficial, scattered, and ambiguous pronouncements on habeas corpus when it acts for preventive purposes. Throughout this thesis, the reader is shown, through research and casuistry, the lack of determination of the Constitutional Court to address the scope, purpose, origin and nature of preventive habeas corpus, a conflictive issue that may have certain repercussions for the constitutional justice system. Thus, and intensive effort has been made to analyze these two types of habeas corpus and how their correct application is favorable for the rights of persons deprived of liberty. The aim is to reduce acts of violence through prevention, without disregarding the efforts that the State and its institutions must make to reform the penitentiary system in a structural manner. For the development of this academic work available to the reader, a methodology integrated by materials, techniques, research methods and documentary observation used in the legal-doctrinaire research, in the surveys and interviews conducted with the legal professionals and in the study of cases selected by the Constitutional Court is applied. Thus, at the end of this academic proposal, its final product is reflected in the conclusions, recommendations and propositional guidelines that will serve as a guide for the application of habeas corpus in its preventive and corrective types. This exercise undoubtedly allows the evolution of the law as society advances and contributes to the strengthening of the national legal culture. Key Words: persons deprived of liberty, jurisprudence, rights, jurisdictional guarantees, constitutional justice.